Answer:
29
Step-by-step explanation:
2x - 14 = x + 15
2x - x = 15 + 14
x = 29
check
44 = 44
Answer:
is the required factorization of f(x).
Step-by-step explanation:
To factor the expression we must first group the terms and then take out common from these groups
![f(x)=x^3+3x^2+16x+48=(x^3+3x^2)+(16x+48)](https://tex.z-dn.net/?f=%20f%28x%29%3Dx%5E3%2B3x%5E2%2B16x%2B48%3D%28x%5E3%2B3x%5E2%29%2B%2816x%2B48%29)
Taking
common from first group and the 16 from second group we get:
![f(x) = x^2(x+3)+16(x+3) = (x+3)(x^2+16)](https://tex.z-dn.net/?f=%20f%28x%29%20%3D%20x%5E2%28x%2B3%29%2B16%28x%2B3%29%20%3D%20%28x%2B3%29%28x%5E2%2B16%29%20)
Now, to factor in complex from we have to break term ![x^2+16](https://tex.z-dn.net/?f=%20x%5E2%2B16)
![f(x)= (x+3){x^2-(-4i)^2}](https://tex.z-dn.net/?f=%20f%28x%29%3D%20%28x%2B3%29%7Bx%5E2-%28-4i%29%5E2%7D%20)
As, ![i^2 = -1 , therefore (-4i)^2 = 16i^2 =-16](https://tex.z-dn.net/?f=%20i%5E2%20%3D%20-1%20%2C%20therefore%20%28-4i%29%5E2%20%3D%2016i%5E2%20%3D-16%20)
Also using identity ![a^2-b^2 =(a+b)(a-b)](https://tex.z-dn.net/?f=%20a%5E2-b%5E2%20%3D%28a%2Bb%29%28a-b%29%20)
On solving
![f(x) = (x+3)(x+4i)(x-4i)](https://tex.z-dn.net/?f=%20f%28x%29%20%3D%20%28x%2B3%29%28x%2B4i%29%28x-4i%29%20)
is the required factorization of f(x).
Answer:
A-B=x^2-x+1
Step-by-step explanation:
A-B=3x^2+5x-6+(-2x^2-6x+7)
=3x^2+5x-6-2x^2-6x+7
=x^2-x+1
Answer:
mean
Step-by-step explanation:
Normal distribution curves Is a distribution curve having different mean values with a standard deviations
the correct option: mean
A normal distribution curve is standardized as follows:
(a) The mean value of the unstandardized curve is made the origin, thus making the mean value, x, zero.
(b) The horizontal axis is scaled in standard deviations. This is done by letting z= x−x/ σ , where z is called the normal standard variate, x is the value of the variable, x is the mean value of the distribution and σ is the standard deviation of the distribution.
2.28 or fraction form 2 7/25
Hope that helped